Light emission from Si-based nano-materials - Manik Dua. (2009)
Silicon is one of the most abundant materials in nature and its desirable electrical, mechanical and chemical properties have made it the main material in the microelectronics industry. However silicon is an indirect semiconductor and therefore an inefficient light emitter. On the other hand, silicon micro-photonics, the evolving technology which combines photonics and silicon microelectronics, requires a silicon-based light source to achieve a fully integrated optoelectronic device compatible with conventional VLSI fabrication technology. In recent years, much of the research effort has been focused on the SRSN films because of their strong light emission and their relatively lower barriers for electrons and holes. Different structures, such as porous silicon and silicon quantum dots embedded in a dielectric matrix, have also been proposed to address this problem. Another approach that utilizes a silicon-based multilayer structure is promising in realizing efficient light emitting devices due to their structural stability and the ability to inject electronhole pairs into the structure efficiently by electric current.